British Society of Gastroenterology guidance for management of inflammatory bowel disease during the COVID-19 pandemic. Issue 6 (17th April 2020) - Kennedy, Nicholas A; Jones, Gareth-Rhys; Lamb, Christopher A; Appleby, Richard; Arnott, Ian; Beattie, R Mark; Bloom, Stuart; Brooks, Alenka J; Cooney, Rachel; Dart, Robin J; Edwards, Cathryn; Fraser, Aileen; et al.
Abstract : The COVID-19 pandemic is putting unprecedented pressures on healthcare systems globally. Early insights have been made possible by rapid sharing of data from China and Italy. In the UK, we have rapidly mobilised inflammatory bowel disease (IBD) centres in order that preparations can be made to protect our patients and the clinical services they rely on. This is a novel coronavirus; much is unknown as to how it will affect people with IBD. We also lack information about the impact of different immunosuppressive medications. To address this uncertainty, the British Society of Gastroenterology (BSG) COVID-19 IBD Working Group has used the best available data and expert opinion to generate a risk grid that groups patients into highest, moderate and lowest risk categories. This grid allows patients to be instructed to follow the UK government's advice for shielding, stringent and standard advice regarding social distancing, respectively. Further considerations are given to service provision, medical and surgical therapy, endoscopy, imaging and clinical trials.